2004
DOI: 10.1007/s00436-004-1189-2
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopy study of Tritrichomonas augusta

Abstract: Tritrichomonas augusta is a flagellated protozoan that parasitizes amphibians and reptiles. According to scanning electron microscopy (SEM), the cell shape of T. augusta varies from slender pyriform to ovoidal. Our data show the morphological features of the trophozoites: the emergence of the anterior flagella, the structure of the undulating membrane and the position and shape of the pelta, axostyle and posterior flagellum. In addition, herein we describe spherical forms which are probably pseudocysts. The de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…Ruffled cells accounted for up to 90% of the cell population; however, time interval experiments showed an increase in the number of smooth cells at 72 h. There was no statistically significant difference in size between the two morphological forms. While ruffled cells are observed in other trichomonads, it is unknown what significance this change in trophozoite surface structure represents (59). While the smooth cell types observed were initially postulated to represent a pseudocystlike stage, experiments to induce pseudocyst formation using adverse environmental growth conditions failed (7).…”
Section: Morphological Characteristics Trophozoitesmentioning
confidence: 99%
“…Ruffled cells accounted for up to 90% of the cell population; however, time interval experiments showed an increase in the number of smooth cells at 72 h. There was no statistically significant difference in size between the two morphological forms. While ruffled cells are observed in other trichomonads, it is unknown what significance this change in trophozoite surface structure represents (59). While the smooth cell types observed were initially postulated to represent a pseudocystlike stage, experiments to induce pseudocyst formation using adverse environmental growth conditions failed (7).…”
Section: Morphological Characteristics Trophozoitesmentioning
confidence: 99%
“…internalize flagella to form pseudocysts. In previous studies using SEM, we also demonstrated the morphology of Trichomonas gallinae and Tritrichomonas augusta and the occurrence of pseudocysts (Tasca and De Carli 2003;Borges et al 2004). True cyst wall is present in few trichomonad species, such as those found in the intestinal trichomonads Trichomonas batrachorum and Trichomitus sanguisugae (Brugerolle 1973) and in the free-living trichomonad Ditrichomonas honigbergii (Farmer 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Pseudocyst formation appears under experimental stress conditions, probably indicating a defense mechanism of the parasite, and it also occurs under natural culture conditions (Granger et al 2000;Pereira-Neves et al 2003). Pseudocysts can be seen in cultures maintained under standard conditions but suffering a stress at some point, such as pH alteration or nutrients depletion, leading the parasite to undergo pseudocyst formation (Borges et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Cells were fixed according to Borges et al (2004) and the grids examined by a scanning electron microscope (model XL-30, Philips). Gram staining was performed (Doetsch, 1981) and motility verified by the SIM (Hydrogen-Sulfide, Indole, Motility; Mac Faddin, 2000) test.…”
Section: Morphology Motility and Electron Microscopymentioning
confidence: 99%